A Fully Phase‐Modulated Metasurface as An Energy‐Controllable Circular Polarization Router. Issue 18 (16th July 2020) - Yuan, Yueyi; Sun, Shang; Chen, Yang; Zhang, Kuang; Ding, Xumin; Ratni, Badreddine; Wu, Qun; Burokur, Shah Nawaz; Qiu, Cheng‐Wei
Abstract: Geometric metasurfaces primarily follow the physical mechanism of Pancharatnam–Berry (PB) phases, empowering wavefront control of cross‐polarized reflective/transmissive light components. However, inherently accompanying the cross‐polarized components, the copolarized output components have not been attempted in parallel in existing works. Here, a general method is proposed to construct phase‐modulated metasurfaces for implementing functionalities separately in co‐ and cross‐polarized output fields under circularly polarized (CP) incidence, which is impossible to achieve with solely a geometric phase. By introducing a propagation phase as an additional degree of freedom, the electromagnetic (EM) energy carried by co‐ and cross‐polarized transmitted fields can be fully phase‐modulated with independent wavefronts. Under one CP incidence, a metasurface for separate functionalities with controllable energy repartition is verified by simulations and proof‐of‐principle microwave experiments. A variety of applications can be readily expected in spin‐selective optics, spin‐Hall metasurfaces, and multitasked metasurfaces operating in both reflective and transmissive modes. Abstract : A general scheme based on a phase‐modulated metasurface for simultaneous and independent manipulation of co‐ and cross‐polarized wavefronts is proposed, which breaks through the inherent limitation of the geometric phase principle and achieves full energy modulation in output fields. The energy proportion between two orthogonal CP output functionalities can also be artificially manipulated as an extra freedom of degree for light manipulation.